“You Reap What You Sow”: A New Perspective on Bullying in Indonesia - Fadilah Humaira, Hani; Yustia Hendrawan, Fath (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Bullying is a serious problem that frequently occurs in school settings. Bullying is a pattern of repeated, intentional behavior that affects students physically, emotionally, and academically. This study aims to identify the causes, effects, and efforts to address bullying at School X in Yogyakarta. The study employed a qualitative narrative method with two teachers and five students as participants. The findings indicate that bullying in the school environment can be triggered by jokes, the environment’s response to the victim’s behavior-which is perceived as deviating from norms-and personal animosity. The resulting impacts are quite serious, ranging from fights among students to victims feeling uncomfortable and choosing to transfer schools. The school’s efforts to address this include establishing a special unit for violence prevention, providing a hotline for reporting bullying cases, and conducting awareness campaigns involving external parties. This study is expected to contribute both theoretically and practically. Theoretically, this study is expected to enrich knowledge and mapping regarding student bullying cases at School X in Yogyakarta. Practically, this study is expected to help teachers and students in dealing with bullying cases.Perundungan merupakan sebuah permasalahan serius yang kerap terjadi di lingkungan sekolah. Perundungan merupakan perilaku berulang yang dilakukan secara sengaja sehingga berdampak pada fisik, emosional, hingga akademik siswa. Penelitian ini bertujuan untuk mencari tahu penyebab, dampak, dan upaya perundungan yang terjadi di Sekolah X Yogyakarta. Penelitian ini dilakukan dengan menggunakan metode kualitatif naratif dengan subjek dua guru dan lima siswa/i. Hasil dari penelitian ini berupa penyebab dari perundungan yang terjadi di lingkungan sekolah dapat dipicu candaan, respons lingkungan terhadap perilaku korban yang dianggap tidak sesuai norma, serta kebencian personal. Dampak yang ditimbulkan cukup serius, mulai dari perkelahian antar siswa hingga korban merasa tidak nyaman dan memilih pindah sekolah. Upaya sekolah dalam menyikapi hal ini berupa membentuk unit khusus pencegahan kekerasan, menyediakan hotline untuk pelaporan kasus perundungan, dan mengadakan sosialisasi yang melibatkan pihak-pihak eksternal. Penelitian ini diharapkan dapat memberikan kontribusi baik secara teoritis dan praktis. Secara teoritis, penelitian ini diharapkan mampu memperkaya pengetahuan dan pemetaan mengenai kasus perundungan siswa di sekolah X Yogyakarta. Secara praktis, penelitian ini diharapkan mampu membantu guru dan siswa dalam menghadapi kasus perundungan.